THE EUROPEAN UNION’S LAWSUIT OVER THE 2020 PROHIBITION OF INDONESIAN RAW NICKEL ORE EXPORTS - Basri, Muhammad Hasan; Ismiyatun (PT. Hafasy Dwi Nawasena, 2024)
This research discusses the reasons behind the European Union's lawsuit against Indonesia regarding the policy to ban the export of raw nickel ore in 2020. The background of Indonesia's ban on the export of nickel ore is part of the national plan to develop the domestic industrial sector, including stainless steel production. Based on this policy, the European Union implemented a foreign policy to sue Indonesia at the WTO, considering it a violation of the provisions of the WTO trade agreement under Article XI:1 of the GATT 1994. The method used in this research is a qualitative descriptive research method employing Robert Ghilpin's theory, which describes foreign policy influenced by domestic industry interests and external influences.The European Union's background as a stainless steel producer makes nickel the most significant value addition for the EU in terms of employment, taxes, investments, and product utility. Nickel's utility for the EU, simultaneously serving as a benefit, lies in high-performance technological products that leverage its characteristics of high heat resistance and durability. The comparison of the income results of the EU industry, which significantly impacts the economy, has experienced a decline since the implementation of Indonesia's export ban policy. Consequently, the European Union filed the lawsuit due to economic interests in the EU's domestic industry, such as labor absorption and financial contributions to the state.